DEPICTION OF RACIAL AND FAMILY PROBLEMS OF AMERICANS IN THE STORY “THANK YOU, MA’AM” BY LANGSTON HUGHES - Aydaraliyeva Malohat Botir qizi (Web of Journals Publishing, 2025)
The American short story is regarded as a milestone in the American literary tradition. Langston Hughes was an outstanding and prolific writer during the period called the Harlem Renaissance of the early 20th century. In his story, Hughes depicted the central theme - power of kindness by revealing how a kind gesture makes softer the heart of a thieving teenage boy.
Keywords: American short story, Harlem Renaissance, Langston Hughes, racial and social problems, African-American’s hardship life, old working woman, teenager, lower social groups.